The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/w12102922
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Unsteady Flow Induced by a Large-Scale Hydropower Station on the Water Level Fluctuation of Multi-Approach Channels: A Case Study of the Three Gorges Project, China

Abstract: Unsteady flow induced by hydropower stations exerts a significant impact on the water level in multi-approach channels, which directly threatens the safe passage of ships. In this study, a one-dimensional and a two-dimensional hydrodynamic model are adopted to simulate the water level fluctuations at the entrance of multi-approach channels and the lower lock head of a ship lift with consideration of initial water surface elevation, base flow, flow amplitude, regulation time, and locations of hydropower station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, hydropower stations with reservoirs can also provide multiple benefits, such as ecological protection, irrigation, and navigation. Moreover, existing studies have shown that the participation of hydropower in peak regulation has adverse effects on the comprehensive benefits of reservoirs Wan et al, 2020;Halleraker et al, 2022). Therefore, the reasonable operation of hydropower stations must also consider the conflict between different tasks.…”
Section: Discussionmentioning
confidence: 99%
“…However, hydropower stations with reservoirs can also provide multiple benefits, such as ecological protection, irrigation, and navigation. Moreover, existing studies have shown that the participation of hydropower in peak regulation has adverse effects on the comprehensive benefits of reservoirs Wan et al, 2020;Halleraker et al, 2022). Therefore, the reasonable operation of hydropower stations must also consider the conflict between different tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the potential role of wetlands for water management and wastewater treatment [33], it is expected that the stormwater and watershed discharge can be alleviated by the installation of constructed wetlands in Kangnung Namdae Stream. In addition, the installed constructed wetlands can improve flow regulation services under the influence of global climate changes which increase the frequency and power of floods [31,32,34]. The installed constructed wetlands in Kangnung Namdae Stream can reduce the frequency and magnitude of floods and decrease runoff and streamflow.…”
Section: Analysis Of the Simulated Temperature And Ss Concentration In Kangnung Namdae Stream Under The Application Of Water Quality Manamentioning
confidence: 99%
“…However, hydropower stations with reservoirs can also provide multiple benefits, such as ecological protection, irrigation, and navigation. Moreover, existing studies have shown that the participation of hydropower in peak regulation has adverse effects on the comprehensive benefits of reservoirs (Pérez-Díaz and Wilhelmi, 2010;Wan et al, 2020;Halleraker et al, 2022). Therefore, the reasonable operation of hydropower stations must also consider the conflict between different tasks.…”
Section: Introductionmentioning
confidence: 99%